Self-Compassion as a Mediator of Social Support and Psychological Well-Being Among 12th Students - Dewi Nurul Hidayah; Fendi Krisna Rusdiana (Universitas Hamzanwadi, 2025)
The matter of psychological well-being (PWB) is of fundamental importance, especially for 12th grade students who frequently face increased academic pressures in conjunction with the difficulties of transitioning to life after graduation. By positioning self-compassion as a mediator, this research explores correlation between social support and PWB of students. The study utilized a quantitative path analysis design and featured selective sampling of 133 12th-grade students from SMA X in Wonogiri Regency. The instruments used included Neff’s Self-Compassion Scale (SCS) consisting of 26 items, Zimet’s Multidimensional Scale of Perceived Social Support (MSPSS) with 12 items, and Ryff’s Psychological Well-Being Scale (RPWB) comprising 18 items. Analysis showed a notable connection between social support and PWB, with self-compassion acting as a key mediating factor. The R² value of 0.363 indicates that social support and self-compassion together are able to explain 36.3% of the variation in students' PWB, factors beyond the scope of this research model account for the remaining 63.7% of the variation. However, the R² value is still considered quite good in psychological research, as PWB is known to be influenced by many complex internal and external factors. Thus, this research model can be considered valid and successful in explaining the relationship between variables according to theoretical expectations. These findings underscore that efforts to enhance students’ PWB should not only focus on strengthening social support within their environment but also on cultivating self-compassion as an attitude of kindness toward oneself, enabling students to better manage academic and personal developmental challenges in a healthy and balanced manner.